I was like a kid full of revenge: self-reported reasons for sexual offending by men who were sexually abused as children. Issue 3 (2nd September 2021) - Lambie, Ian; Reil, Jerome
ABSTRACT: It is widely acknowledged that the rate of childhood sexual abuse (CSA) reported by men who sexually offend is elevated relative to the general population. The idea of a "sexually abused-sexual abuser" (SA-SA) cycle is one possible explanation for the relationship between CSA and subsequent sexual offending. The current study explored why sexually abused men went on to sexually offend, through qualitative interviews with 41 SA-SAs attending a community treatment programme in New Zealand. Most of them gave externalising reasons for offending (including anger and revenge towards others, and deviant arousal). There was an even split between those who did/did not see a relationship between their own victimisation and their offending. Of those who perceived this connection, sexualisation, externalisation, and normalisation were themes underlying their motivation to offend. The implications for the treatment of male victims of sexual abuse are discussed.